Ergatives Move Too Early: On an Instance of Opacity in Syntax. (19th October 2015) - Assmann, Anke; Georgi, Doreen; Heck, Fabian; Müller, Gereon; Weisser, Philipp
Abstract: We examine the ban on Ā‐movement of the external argument of a transitive verb that holds in many morphologically ergative languages. We argue that the prohibition against movement of the ergative subject should not be derived from restrictions on the movement of the ergative DP. Rather, we suggest that movement of the ergative argument is per se unproblematic, but if it applies, it applies too early and thereby creates problems for its absolutive co‐argument, which does not receive structural case. In morphologically accusative languages, no such movement asymmetry arises because arguments move too late to trigger the fatal consequences that moving ergatives cause. We present a co‐argument‐based analysis that implies a strictly derivational syntax in which the order of operations plays an important role in deriving properties of the grammar. The analysis also involves an instance of syntactic opacity that (all things being equal) cannot be captured by representational means, thus lending support to a derivational approach to syntax.